Rancang Bangun Tongkat Teleskopik Vacuum Leka VC327 Jaring Laba-Laba Berbasis IoT Dengan Monitoring Android - Hayadi Hamuda; Anjar Setiawan; Fauzan Dika (CV. Sekawan Siji, 2026)
This research aims to develop and evaluate the performance of SCONER (Smart Cobweb Cleaner), an Internet of Things (IoT)-based cobweb cleaning tool for hard-to-reach areas. This tool is equipped with a 1–3 meter telescopic pole, a 2 MP ESP32 camera, an ILI9488 LCD screen for wireless monitoring, and a TP5100 module connected to Firebase for real-time battery monitoring. SCONER uses a 3000 mAh vacuum battery and a 6000 mAh camera battery with a total weight of approximately 1.3 kg, making it lightweight and easy to use. The research method includes system design and testing the tool's performance in cleaning cobwebs and dust. The test results show that SCONER is able to work effectively, facilitate the cleaning process in hard-to-reach areas, and supports real-time monitoring of power usage. This tool has the potential to be a practical solution for household cleaning needs and professional cleaning services.